Genus Tetradium L.: A comprehensive review on traditional uses, phytochemistry, and pharmacological activities. (1st March 2019) - Zhao, Zefeng; He, Xirui; Han, Wei; Chen, Xufei; Liu, Peiliang; Zhao, Xue; Wang, Xing; Zhang, Lixin; Wu, Shaoping; Zheng, Xiaohui
Abstract: Ethnopharmacological relevance: The dried fruit of Tetradium ruticarpum is frequently utilized as a common traditional medicine in China, Japan and Korea. It has been widely used for the treatment of various diseases such as headache, menorrhalgia, dermatophytosis, celialgia, emesis and aphtha and so on. Aim of this review: Despite the wide biological activities of Tetradium plants, there is no current review summarizing medicinal properties of the genus of plants; thus, this review aims to systematically summarize studies on botanical characteristics, traditional uses, phytochemical ingredients, quality control, pharmacokinetics, pharmacological activities and toxicity of Tetradium species to demonstrate their therapeutic capacity. Materials and methods: Information and materials related to Tetradium species were obtained from scientific databases such as Google Scholar, Wikipedia, Web of Science, PubMed, ScienceDirect, ACS Publications, SciFinder. Information was also gathered from International Plant Names Index, Global Biodiversity Information Facility, Chinese Pharmacopoeia and Traditional Chinese Medicine classics, etc. All studies of this genus were included in this review until July 2018. Results: Tetradium is widely assessed regarding its phytochemistry and biological activities. Approximately 131 chemical compounds, including alkaloids, saponins, phenols and other compounds, have been isolated from Tetradium plants. Among these components, alkaloid evodiamine is the most representative active ingredients of Tetradium plants. These compounds isolated from Tetradium plants exhibit a wide range of biological activities in vitro and in vivo including antitumor, antibacterial, anti-inflammatory, insecticide, cardioprotective and lipid-lowering, treating CNS disorders, digestive system regulation and endocrine system improving activities. Furthermore, alkaloids could be used as markers for quality identification and evaluation of medicinal materials and their preparations. Information on evaluating the safety and pharmacokinetics of Tetradium often focuses on the alkaloids, thus further study and clinical data are required to enable the drug safety of the utilization of Tetradium plants. Conclusions: Phytochemical and pharmacological studies of Tetradium plants have proved Tetradium plants are important medicinal herb resource. However, well-designed randomized clinical trials are necessary to confirm the therapeutic benefits of this genus in clinical settings.